Arthroscopic Assessment of Syndesmotic Instability in the Sagittal Plane in a Cadaveric Model. (February 2020) - Lubberts, Bart; Massri-Pugin, Jafet; Guss, Daniel; Wolf, Jonathon C.; Bhimani, Rohan; Waryasz, Gregory R.; DiGiovanni, Christopher W.
Background: Syndesmotic instability is multidirectional, occurring in the coronal, sagittal, and rotational planes. Despite the multitude of studies examining such instability in the coronal plane, other studies have highlighted that syndesmotic instability may instead be more evident in the sagittal plane. The aim of this study was to arthroscopically assess the degree of syndesmotic ligamentous injury necessary to precipitate fibular translation in the sagittal plane. Methods: Twenty-one above-knee cadaveric specimens underwent arthroscopic evaluation of the syndesmosis, first with all syndesmotic and ankle ligaments intact and subsequently with sequential sectioning of the anterior inferior tibiofibular ligament (AITFL), the interosseous ligament (IOL), the posterior inferior tibiofibular ligament (PITFL), and deltoid ligament (DL). In all scenarios, an anterior to posterior (AP) and a posterior to anterior (PA) fibular translation test were performed under a 100-N applied force. AP and PA sagittal plane translation of the distal fibula relative to the fixed tibial incisura was arthroscopically measured. Results: Compared with the intact ligamentous state, there was no difference in sagittal fibular translation when only 1 or 2 ligaments were transected. After transection of all the syndesmotic ligaments (AITFL, IOL, and PITFL) or after partial transection of the syndesmotic ligaments (AITFL, IOL) alongside the DL, fibular translation in the sagittal plane significantly increased as compared with the intact state ( P values ranging from .041 to <.001). The optimal cutoff point to distinguish stable from unstable injuries was equal to 2 mm of fibular translation for the total sum of AP and PA translation (sensitivity 77.5%; specificity 88.9%). Conclusion: Syndesmotic instability appears in the sagittal plane after injury to all 3 syndesmotic ligaments or after partial syndesmotic injury with concomitant deltoid ligament injury in this cadaveric model. The optimal cutoff point to arthroscopically distinguish stable from unstable injuries was 2 mm of total fibular translation. Clinical Relevance: These data can help surgeons arthroscopically distinguish between stable syndesmotic injuries and unstable ones that require syndesmotic stabilization.